2005
DOI: 10.2188/jea.15.s126
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pepsinogen Values and Helicobacter pylori Status among Control Subjects of a Nested Case-Control Study in the JACC study

Abstract: BACKGROUD: Helicobacter pylori infection and serum pepsinogen values are strongly related with stomach cancer. The aim of this study was to know what were these factors among general population. METHODS: Subjects were randomly selected 633 control subjects in a nested case-control study for risk of stomach cancer. Most of them were from rural areas of Japan. Using frozen sera, pepsinogen I (PG I) and II (PG II) values and H. pylori antibody were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
5
16
0
Order By: Relevance
“…Our present study demonstrated that patients with H. pylori ‐related non‐AG (i.e. SG and SG‐IM), showed significantly greater levels of sPGII than their H. pylori ‐seronegative counterparts, which was in general agreement with previous reports 31,32 . A positive correlation between sPGII and H. pylori status was also observed in patients with GC or precancerous lesions (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Our present study demonstrated that patients with H. pylori ‐related non‐AG (i.e. SG and SG‐IM), showed significantly greater levels of sPGII than their H. pylori ‐seronegative counterparts, which was in general agreement with previous reports 31,32 . A positive correlation between sPGII and H. pylori status was also observed in patients with GC or precancerous lesions (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Measurement of pepsinogen serum levels was carried out by 11 studies in Japan (33,35,44,49,(51)(52)(53)(55)(56)(57)(58), two studies among Japanese living abroad (48,50), several others in Europe [United Kingdom (31,40), Italy (32), Finland (43,46,54) and the Netherlands (47)], two in the United States (29,45), and one in New Zealand (59). International comparative studies included population samples from 13 (37), 4 (60), and 2 (42) nations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the cutoff values widely differed among the studies: 70 ng/mL (indicating mild, moderate, and severe CAG) was most frequently used as PG I threshold, but there are also studies using 17, 20, or 25 ng/mL (indicating exclusively severe CAG) and one study each with 30, 49, and 50 ng/mL, a pattern that inevitably leads to differences in prevalence estimates. In contrast, the threshold for the PG I/PG II ratio was 3.0 (or 2.9) mostly, but a threshold of 1.3, 1.6, 2.0, and 2.5 was also used in single studies (40,42,47,49,58).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the percentages of those with severe serological atrophy increased with age from 10% in those aged 40-49 years to 38% in those aged 70 and more, and the percentages of those with mild serological atrophy were about 30%, independent of age. 68 Although the prevalence of H. pylori infection in Japan has fallen in recent years, 22 those who are infected remain at risk of gastric cancer. An H. pylori infection was detected in up to 70% of the population by the age of 40 years in Japan.…”
Section: Advantages and Disadvantages Of Serum Pepsinogen Methodsmentioning
confidence: 99%
“…67 reported that among subjects younger than 40 years old, early stage carcinoma has a stronger association with H. pylori than advanced carcinoma, and intestinal‐ and diffuse‐type carcinomas have an association with H. pylori . It has been demonstrated that the percentages of those with severe serological atrophy increased with age from 10% in those aged 40–49 years to 38% in those aged 70 and more, and the percentages of those with mild serological atrophy were about 30%, independent of age 68 . Although the prevalence of H. pylori infection in Japan has fallen in recent years, 22 those who are infected remain at risk of gastric cancer.…”
Section: Gastric Cancer Screeningmentioning
confidence: 99%